Identity Politics In Wali Nagari Silantai Election - Arif Hardika Putra; Irawati Irawati; Andri Rusta; Mhd Fajri (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
The purpose of this study is to provide information related to identity politics not only occurs at the election and election level but also occurs in the nagari wali election or abbreviated as PILWANA in Nagari Silantai Tahun 2019. Italso aims to discuss the main forms of identity politics of candidates or political elites. a way to gain power in a position. Therefore, the study revealed tribal emblems, regional identities (jorong) using the community tokoh network and the winning team that had the same place of birth and raised in the election of wali nagari.